Elucidating the electrochemical mechanism for enhanced corrosion of Ti3C2Tx-coated mild steel. (2nd September 2021) - Cai, Meng; Yan, Han; Li, Yuting; Li, Wen; Fan, Xiaoqiang; Zhu, Minhao
Abstract: Two-dimensional (2D) transition metal carbides, carbonitrides and nitrides (MXenes) represent a burgeoning group of 2D layered materials with widespread applications due to unique performance characteristics, in which titanium carbide (Ti3 C2 Tx ) as corrosion inhibitor provides good physical barrier effect. Given that, as-prepared Ti3 C2 Tx MXene via chemical etching of titanium aluminium carbide (MAX) phase using HF/oxidants have good corrosion resistance of their own, but it is of inevitable importance to understand the effect of their hydrophilic surfaces and high electrical conductivities on corrosion of alloy substrate. Herein Ti3 C2 Tx MXene coating was prepared on mild steel substrate (Q345) to explore its corrosion behaviors in different conditions. The corrosion current density ( i corr ) of MXene-coated Q345 was 6.39 × 10 –6 A · cm −2, which was higher than that of uncoated Q345 sample (5.66 × 10 –6 A · cm −2 ). After 3 days of storage in wet environment of 40% and 90% relative humidity (RH) at 30 °C, MXene-coated Q345 had suffered from a higher degree of spatially inhomogeneous corrosion, while the surface of uncoated substrate was still neat and glossy in spite of undergoing 1 month of storage under the same condition. The results demonstrate that Ti3 C2 Tx MXene accelerates the corrosion of Q345. Conductive and hydrophilic Ti3 C2 Tx could act as an electrode to propagate the charge generated by the oxidation of Fe, which forms a micro corrosion cell with substrate. Thus, the electrochemical corrosion process of substrate is accelerated.